Molecular analysis of 12 Chinese patients with 11β‐hydroxylase deficiency and in vitro functional study of 20 CYP11B1 missense variants. Issue 4 (17th March 2023) - Sun, Bang; Lu, Lin; Xie, Shaowei; Zhang, Wei; Zhang, Xiaoxia; Tong, Anli; Chen, Shi; Wu, Xueyan; Mao, Jiangfeng; Wang, Xi; Qiu, Ling; Nie, Min
Abstract: Steroid 11β‐hydroxylase deficiency (11β‐OHD) is a rare autosomal recessive disorder caused by pathogenic variants of CYP11B1 gene. This study aimed to perform molecular analysis of a Chinese 11β‐OHD series and in vitro functional study of twenty CYP11B1 missense variants. Twelve Chinese patients with clinical diagnosis of 11β‐OHD were included in the study to analyze their molecular etiology. Genomic DNA of patients was extracted to be sequenced all coding exons and intronic flanking sequences of CYP11B1 . Fourteen missense variants found in 12 patients mentioned above along with 6 missense variants previously reported by our team were evaluated functionally. Amino acid substitutions were analyzed with computational program to determine their effects on the three‐dimensional structure of CYP11B1 protein. Clinical characteristics and hormone levels at baseline of the 18 patients carrying 18 missense variants aforementioned were recorded to perform genotype–phenotype correlation. A total of 21 rare variants including 9 novel and 12 recurrent ones were identified in 12 patients, out of which 17 were missense, 2 were nonsense, 1 was a splice site variant, and 1 was a deletion–insertion variant. Results of in vitro functional study revealed that 3 out of 20 missense mutants (p.Leu3Pro, p.Gly267Ser, and p.Ala367Ser) had partial enzyme activity and the other 17 had little enzymatic activity. The impairment degree of enzymatic activity in vitro functional study was also reflected in the severity degree of interaction change between the wild‐type/mutant‐type amino acid and its adjacent amino acids in three‐dimensional model. In conclusion, the addition of 9 novel variants expands the spectrum of CYP11B1 pathogenic variants. Our results demonstrate that twenty CYP11B1 variants lead to impaired 11β‐hydroxylase activity in vitro. Visualizing these variants in the three‐dimensional model structure of CYP11B1 protein can provide a plausible explanation for the results measured in vitro. Abstract : A total of 21 rare variants were identified in 12 Chinese patients with 11β‐OHD, out of which 17 were missense, 2 were nonsense, 1 was a splice site variant, and 1 was a deletion–insertion variant. Twenty missense variants were evaluated functionally, and the results showed that 3 had partial enzyme activity and the other 17 had little.